PENGECORAN BAHAN CETAKAN PERMANEN TELAPAK KAKI PALSU - M. Rizky Dwi Yanza (ELEMEN : JURNAL TEKNIK MESIN, 2025)
Molds of prosthetic feet can be made using aluminum materials by the metal casting method. This research aims to create a pattern design of molding materials for prosthetic feet that can reduce the use of the amount of material and time efficiency in making casting patterns. The creation of pattern design relies on the use of CAD software which is used as a reference for making prototypes to be produced through a machining process with the use of CAM technology on CNC machines to ensure the desired level of precision in sand casting trials. The results of this study show that the pattern prototype of the prosthetic sole molding material can meet the design specifications with a high degree of precision and function as an effective molding material.